اٹھارویں صدی میں فہم قرآن کا ارتقا:امام شاہ ولی اللہ دہلوی کے کام کا تحقیقی مطالعہ: The Evolution of Understanding of the Quran in the 18th Century: The Specific Study of Imam Shah Wali Ullah,s Works - Muhammad Anas Hassan; Dr. Saeed Ul Rehman; Dr. Abdul Qadir Buzdar (MEI, 2022)
Mughal Empire in Sub-Continent was deteriorating, but simultaneously a sun of knowledge, research and Ijtihad was emerged and enlightened with its enchenanting light not only Sub-Continent but the whole Muslim world. The Sun was no other than Imam Shah Wali ullah Dahelvi who was born in 1703 AD. Shah Wali Ullah tried to the make comprehension of Quran easy for common people. He considered, the conveyance of the true message of Quran to the commoners, as an important need of the age. Shah Wali ullah wrote ‘Muqadamma Fatah ul Rehman’ "مقدمہ فتح الرحمٰن", "الفوزالکبیرفی اصول تفسیر" and "تاویل الاحادیث". In these books, he gave priciples of tafseer (explanation of Quran) and gave new heights to the old knowledge and skill of tafseer of Quran.The effects of these books on the later tafaseer (explanation of Quran) written after 18th century, are clearly visible.